Case Report: Clinical application of continuous arterial infusion chemotherapy in neoadjuvant therapy for locally advanced gastric cancer - Lin, Wenli; Huang, Zhongxian; Du, Zhenhua; Wang, Yunshan; Zuo, Taiyang (Frontiers in Oncology, 2023)
Platinum-fluorouracil combination chemotherapy is the standard neoadjuvant treatment for locally advanced gastric cancer in China, but it does not improve the survival benefit of patients. In recent years, the application of immune checkpoint inhibitors and/or targeted drugs in neoadjuvant therapy for gastric cancer has achieved certain efficacy, but the survival benefit of patients is still not obvious. Intra-arterial infusion chemotherapy, as a method of regional therapy, has been widely used in the treatment of many advanced tumors and achieved remarkable curative effect. The role of arterial infusion chemotherapy in neoadjuvant therapy for gastric cancer is not clear. We describe two patients with locally advanced gastric cancer treated with continuous arterial infusion neoadjuvant chemotherapy. Two patients received continuous arterial infusion of chemotherapy drugs for 50 hours, the drugs were pumped into the main feeding artery of the tumor through the arterial catheter. A total of 4 cycles were followed, then undergone surgical resection. The postoperative pathological pCR of two patients was 100%, TRG was 0 grade, and no further anti-tumor therapy was required after operation, achieving clinical cure. During the treatment period, no serious adverse events occurred in either patient. These results suggest that continuous arterial infusion chemotherapy may be a new adjuvant therapy for locally advanced gastric cancer.